Sufi Elements in Ki Hadjar Dewantara’s Education Method - Taufikin Taufikin (ADDIN, 2021)
The 5.0 social era has changed the face of global education, including in Indonesia, which has given impacts to its young generation. As a matter of fact, the Indonesian youths merely use their intellectual skills to explore the technological advancement while neglecting the values of virtue, character, and attitude. Thus, it is necessary to recall the thoughts of the Indonesian prominent scholar Ki Hadjar Dewantara who combined multidiciplinary sciences and Indonesian local values as a reference to solve the aforementioned problem. This study is a library research which aims at investigating thoroughly his thoughts, especially ones concerning with the educational theories as well as interpreting the unstructured existing methods used in Indonesian education. The results show that Ki Hadjar Dewantara presented educational ideas from the perspective of multidiciplinary sciences, especially from Sufi Elements in Islam. Ki Hadjar Dewantara introduced this method in three levels: Firstly, children aged 0-7 can be given sharia-packaged exemplary and habituation methods. Secondly, children aged 7-14 can be given hakikat method which applies reward and punishment. Thirdly, students aged 14-21 can be given tirakat and ma’rifat methods which apply physical and mental learning experiences.